Rationale for the preservation of vital pulp in the use of fixed dentures in the experiment - Inna Pustokhina, Andrey Sevbitov, Aleksei Dorofeev, Kirill Ershov, Yulianna Enina,; Zhad’ko, Sergey (Opción, 2020)
The study aims to investigate rationale for the preservation of vital pulp in the use of fixed dentures in the experiment. In study, a comparison of traditional and air-abrasive methods of preparation was carried out in the laboratory. As a result, it was revealed that the air-abrasive method is more sparing to the tissues of the tooth, preserving the integrity of the dentin and enamel. In conclusion, the results of enamel X-ray microanalysis confirmed that content of the chemical elements F, P, Ca in healthy dental tissue is within the given ratio, but it significantly depends on the preparation technique.